Genetic characterisation of multidrug-resistant Salmonella enterica serotypes isolated from poultry in Cairo, Egypt - Mohammed Abdel-Maksoud; Rania Abdel-Khalek; Atef El-Gendy; Rawia F. Gamal; Hemmat M. Abdelhady; Brent L. House (AOSIS, 2015)
Background: Food-borne diseases pose serious health problems, affecting public health and economic development worldwide. Methods: Salmonella was isolated from samples of chicken parts, skin samples of whole chicken carcasses, raw egg yolks, eggshells and chicken faeces. Resulting isolates were characterised by serogrouping, serotyping, antimicrobial susceptibility testing and detection of extended-spectrum β-lactamase (ESBL) production. Antibiotic resistance genes and integrons were identified by polymerase chain reaction (PCR). Results: The detection rates of Salmonella were 60%, 64% and 62% in chicken parts, skin, and faeces, respectively, whereas the egg yolks and eggshells were uniformly negative. Salmonella Kentucky and S. Enteritidis serotypes comprised 43.6% and 2.6% of the isolates, respectively, whilst S. Typhimurium was absent. Variable resistance rates were observed against 16 antibiotics; 97% were resistant to sulfamethoxazole, 96% to nalidixic acid and tetracycline and 76% to ampicillin. Multidrug resistance was detected in 82% (64/78) of the isolates and ESBL production was detected in 8% (6/78). The β-lactamase blaTEM-1 gene was detected in 57.6% and blaSHV-1 in 6.8% of the isolates, whilst the blaOXA gene was absent. The sul1gene was detected in 97.3% and the sul2 gene in 5.3% of the isolates. Sixty-four of the 78 isolates (82%) were positive for the integrase gene (int I) from class 1 integrons, whilst int II was absent. Conclusion: This study reveals the presence of an alarming number of multidrug-resistant Salmonella isolates in the local poultry markets in Cairo. The high levels of drug resistance suggest an emerging problem that could impact negatively on efforts to prevent and treat poultry and poultry-transmitted human diseases in Egypt.